Five-years review of obstetric hysterectomy at tertiary care center - Pawar, Anita G.; Shinde, Mangala A.; M., Sarasjothi; Nemagouda, Priyanka B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Obstetric hysterectomy (OH) is indicated as last resort operation to save the life of the mother and associated with high complication rates, so requires a highly experienced and skilled medical team ,to solve any complication. Objective was to identify incidence, demographic profile, indications, risk factors, complications, maternal morbidity and mortality associated with obstetric hysterectomy. Methods: Retrospective analytical study of 47 case records is done over period of last 5 years from October 1st October 2015 to 30th September 2020 at VDGIMS, a tertiary care center, Latur. Results are expressed in frequency and percentages. Results: In our study, the rate of OH was 1.1/1000 deliveries. Most common (68%) age group was 21-30 yrs, majority (70%) were multipara, and booked (76%). Most common indication of OH was atonic PPH (65%), followed by traumatic PP, including rupture uterus (21%), and placenta acreta (10%). Most OH was performed on emergency basis (91%) and of subtotal type (95%). Major mode of delivery was cesarean 65% and vaginal delivery in 21% cases. Most common risk factors were placental causes (55%), previous LSCS (48%) and hypertensive disorder (31%). High maternal morbidity in form of 100% blood transfusion rate, 93% ICU admission, inotropes and ventilator support in 59% cases and prolonged hospital stay in 75% cases seen. Most common complication were hemorrhagic shock 21%, DIC (29%), renal failure (12%) and septic shock (14%) with maternal death rate of 23% was noted. Conclusions: Obstetric hysterectomy is a necessary life-saving operation, but also associated with high maternal morbidity and mortality, which can be minimized with timely done procedure by experienced person.